1995
DOI: 10.1002/j.1460-2075.1995.tb00129.x
|View full text |Cite
|
Sign up to set email alerts
|

IgM receptor-mediated transactivation of the IgH 3′ enhancer couples a novel Elf-1-AP-1 protein complex to the developmental control of enhancer function.

Abstract: The function of the temporally regulated B lymphocytespecific immunoglobulin heavy chain (IgH) 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 61 publications
2
45
0
Order By: Relevance
“…Considering the body of evidence that suggests that Ets/AP-1 cooperate for full transcriptional activation, it seems likely that this may be the function of the Ϫ76/Ϫ58 element. For instance similar cooperation between Ets and AP-1 occurs through a juxtaposed Ets/AP-1-binding site in the polyoma virus enhancer (18) and has subsequently been implicated in the regulation of genes involved in invasion and metastasis, including collagenase and urokinase plasminogen activator (19,(33)(34)(35)(36)(37). Although we found that the collagenase Ets element or the polyoma virus Ets element did not effectively compete for binding to the FGF-BP Ets element, this may reflect the binding of another Ets family member to the FGF-BP promoter whose recognition site could be determined by sequences flanking the GGA core (27).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the body of evidence that suggests that Ets/AP-1 cooperate for full transcriptional activation, it seems likely that this may be the function of the Ϫ76/Ϫ58 element. For instance similar cooperation between Ets and AP-1 occurs through a juxtaposed Ets/AP-1-binding site in the polyoma virus enhancer (18) and has subsequently been implicated in the regulation of genes involved in invasion and metastasis, including collagenase and urokinase plasminogen activator (19,(33)(34)(35)(36)(37). Although we found that the collagenase Ets element or the polyoma virus Ets element did not effectively compete for binding to the FGF-BP Ets element, this may reflect the binding of another Ets family member to the FGF-BP promoter whose recognition site could be determined by sequences flanking the GGA core (27).…”
Section: Discussionmentioning
confidence: 99%
“…Since this initial description, the transcriptional activation of other genes has also been shown to require RREs. Rasstimulated RRE promoter elements are able to activate the expression of genes known to be involved in cellular transformation and migration, including uPA, stromelysin-1 (MMP-3) and collagenase-1 (MMP-1) (Aoyama and Klemenz, 1993;Bortner et al, 1993;Chambers and Tuck, 1993;Grant et al, 1995;Wasylyk et al, 1991;Wu et al, 1994). Ras-responsiveness can be blocked by dominant-negative members of the AP1 and Ets families (Bortner et al, 1993;Galang et al, 1994;Gutman and Wasylyk, 1991;Langer et al, 1992;Lloyd et al, 1991;Wasylyk et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The factors Ets-1, Elf-1, and PU.1 bind to various sites within the IgH intronic enhancer (10 -12). The 3Ј regulatory region contains binding sites for both Elf-1 and PU.1 (13,14). The Ets transcription factor PU.1 is predicted to be important in B cell development based on two observations.…”
mentioning
confidence: 99%